A New Formal Synthetic Route to Entecavir - Liu, Lixia; Sun, Yongli; Wang, Jiwu; Ou, Wentao; Wang, Xiaoji; Huang, Shuangping (Synlett, 2019)
We describe a new and straightforward approach to the formal synthesis of the hepatitis B virus inhibitor entecavir, an important hepatitis B drug, in ten steps overall. Key features of the route are a Morita–Baylis–Hillman reaction, a Sharpless asymmetric epoxidation, a reductive epoxide opening of an α,β-epoxy ketone, and a Riley selenium dioxide oxidation.
Keywords: entecavir; formal synthesis; epoxy ketones; Sharpless epoxidation; ring cleavage; Riley oxidation